The elusiveness of imagination : a case study of five teachers' conceptions and enactments of imaginative writing pedagogies in Gauteng classrooms. - Mendelowitz, Belinda (My University, 2010)
This thesis explores the relationship between teachers’ conceptions of imagination and imaginative writing and how they enact these ideas in the classroom. The three primary research questions are (1) how do teachers conceptualise the imagination and imaginative writing? (2) how are these ideas and beliefs enacted through classroom writing practices? (3) what is the relationship between teachers’ conceptions of imaginative writing and their enactment of imaginative writing pedagogy in the classroom? I argue that imagination and imaginative writing have been sidelined in South African educational discourses and that a narrow view of imagination prevails. Drawing on Vygotsky’s work on imagination, writing pedagogy theorists and philosophical ideas, I argue for a nuanced model of imaginative writing which synthesises higher-level thinking, affect and creativity. This study uses a multiple case study methodology. In order to answer the first research question, I conducted in-depth interviews with five intermediate phase teachers. I then observed their English classes, two weeks per teacher, to gain insights into the second and third research questions. I also gathered and analysed samples of learners’ writing to explore the impact of teachers’ pedagogies on learners’ writing. Thus, enactment of imaginative writing pedagogies is explored from various angles. The findings suggest that there is a complex relationship between teachers’ personal writing histories, their conceptions of imaginative writing and classroom practice. One of the central findings of this thesis is that teachers’ personal writing practices have less of an impact on their imaginative writing pedagogy than one would expect. Teachers’ conceptualisations of imagination and their related beliefs and attitudes have a more significant impact on their pedagogy than their personal writing practices. However, values and beliefs that embrace imaginative writing, while a necessary precondition for productive practice, are not necessarily enough. These need to be coupled with a well-developed pedagogy and implemented in institutional contexts that are conducive to imaginative writing. Teachers draw on a range of different discourses to construct their ideas about imaginative writing and their practice. While the discourses articulated in the interviews were iii significant, at times there were tensions between teachers’ espoused and enacted practice and in some instances contradictory discourses operating in the interview and in their classrooms. The findings of this thesis highlight the importance of key elements of practice working together, pulling in the same direction and being framed by reinforcing discourses. At times all five teachers drew on imaginative discourses (i.e. discourses that value imaginative writing and thinking, and that regard it as central to learning), and strove to promote imaginative writing. However, the ultimate effectiveness of this was largely determined by the manner in which imaginative discourses were sustained and integrated with other discourses.